A case of mixed adenoneuroendocrine carcinoma of the gallbladder arising from an intracystic papillary neoplasm associated with pancreaticobiliary maljunction. (22nd August 2014) - Meguro, Yoshiyuki; Fukushima, Noriyoshi; Koizumi, Masaru; Kasahara, Naoya; Hydo, Masanobu; Morishima, Kazue; Sata, Naohiro; Lefor, Alan T.; Yasuda, Yoshikazu
<x xml:space="preserve">Abstract</x> A 54‐year‐old Japanese woman was referred with a gallbladder tumor. Based on the results of the computed tomography scan, endoscopic retrograde cholangiopancreatography, and magnetic resonance cholangiopancreatography, a mucin‐producing neoplasm of the gallbladder associated with pancreaticobiliary maljunction was diagnosed. Extended cholecystectomy, extrahepatic bile duct resection, and choledochojejunostomy were performed, and she remains free of recurrence 24 months after resection. Histopathological examination revealed that the papillary component of the lesion was an intracystic papillary neoplasm with diverse characteristics of pancreaticobiliary epithelium and intestinal epithelium including mucin. In this component, most of the papillary lesion was a high‐grade intraepithelial neoplasm, but also showed slight invasion into the muscular layer. The nodular component consisted of both poorly differentiated biliary type adenocarcinoma and large cell neuroendocrine carcinoma. We report a rare case of a mixed adenoneuroendocrine carcinoma arising from an intracystic papillary neoplasm associated with pancreaticobiliary maljunction. As for the histogenesis of this tumor, based on the histopathologic appearance, transdifferentiation from poorly differentiated biliary type adenocarcinoma to large cell neuroendocrine carcinoma is considered the most possible histogenesis of this tumor.